2023
DOI: 10.1177/24730114231153153
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Review: Autograft Bone Use in Foot and Ankle Surgery

Abstract: Bone autografts are frequently harvested for use in foot and ankle surgery. A commonly used harvest site is the iliac crest; however, because of known morbidity with this site, the tibia and calcaneus are attractive alternatives. There remains limited understanding regarding the osteogenic potential of autografts from each of these locations. In this review, we provided an update of the known data on bone autografts from the iliac crest, tibia, and calcaneus, focusing on the total cells harvested from each sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…Bone autograft and orthobiologics are commonly used for arthrodesis procedures about the foot and ankle to optimize union rates. 13,15,20 Buda et al 3 evaluated 189 TMT joints and found that the use of bone autograft significantly lowered the risk of nonunion (OR = 0.2). Not surprisingly, our results demonstrated that the use of bone graft was a positive predictor of union.…”
Section: Discussionmentioning
confidence: 99%
“…Bone autograft and orthobiologics are commonly used for arthrodesis procedures about the foot and ankle to optimize union rates. 13,15,20 Buda et al 3 evaluated 189 TMT joints and found that the use of bone autograft significantly lowered the risk of nonunion (OR = 0.2). Not surprisingly, our results demonstrated that the use of bone graft was a positive predictor of union.…”
Section: Discussionmentioning
confidence: 99%